2014
DOI: 10.1136/vr.101961
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vaccination againstActinobacillus pleuropneumoniaein two Belgian farrow‐to‐finish pig herds with a history of chronic pleurisy

Abstract: The efficacy of an Actinobacillus pleuropneumoniae subunit vaccine based on ApxIA, ApxIIA, ApxIIIA and OMP-2 (Porcilis App, MSD) was investigated in two farrow-to-finish pig herds (A and B) affected by chronic pleurisy. In total, 1161 pigs were included. At three weeks of age, the pigs were randomly allocated to non-vaccinated control (NV; n=580) and vaccinated (V; n=581) groups. At 6 and 10 weeks of age, pigs were injected with Porcilis-APP (V group) or adjuvant (NV group). At slaughter (26 weeks), pleurisy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…In Canada, vaccines are routinely recommended and applied in livestock production systems (Codes of Practice for the care and handling of farm animals [n.d.]; https://www.nfacc.ca/codes-of-practice). Studies have reported the relationship between vaccination and antimicrobial use (Del Pozo Sacristán, Michiels, Martens, Haesebrouck, & Maes, ; Fertner, Toft, Martin, & Boklund, ; Lava, Schüpbach‐Regula, Steiner, & Meylan, ); however, an assessment of these combined actions on the occurrence of resistance has not been published to our knowledge. The absence of vaccination and other nonantimicrobial use factors at the farm level of the agri‐food chain in this review represents an important data gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, vaccines are routinely recommended and applied in livestock production systems (Codes of Practice for the care and handling of farm animals [n.d.]; https://www.nfacc.ca/codes-of-practice). Studies have reported the relationship between vaccination and antimicrobial use (Del Pozo Sacristán, Michiels, Martens, Haesebrouck, & Maes, ; Fertner, Toft, Martin, & Boklund, ; Lava, Schüpbach‐Regula, Steiner, & Meylan, ); however, an assessment of these combined actions on the occurrence of resistance has not been published to our knowledge. The absence of vaccination and other nonantimicrobial use factors at the farm level of the agri‐food chain in this review represents an important data gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, temporary assistance by an external coach/veterinarian may be helpful. The role of the veterinarian as a coach and the constraints herein, as described above, have been described in ruminant veterinary medicine (Lindberg and Houe, 2005;Smith and Hollis, 2007;Derks et al, 2011;Hakansson et al, 2011) and to a lesser extent in porcine veterinary medicine (Alarcon et al, 2014). The coach in this study was not paid by the farmer.…”
Section: Discussionmentioning
confidence: 99%
“…To be able to achieve this reduction, it is important to assist and guide farmers in this process, as they are generally aware of the problems and risks, but not sufficiently knowledgeable on the implications on herd level (Visschers et al., ). They are generally also willing to reduce their antimicrobial use but are unfamiliar with alternative solutions such as biosecurity improvements (Laanen et al., ; Postma et al., ; Postma et al., ) and improved immunization through vaccination against infections such as ileitis (Adam, ; Coube et al., ), porcine proliferative enteropathy (Bak and Rathkjen, ), porcine circovirus (Brockhoff et al., ; Aerts and Wertenbroek, ; Coube et al., ; Koenders and Wertenbroek, ) and Actinobacillus pleuropneumoniae (Del Pozo Sacristán et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, serotype 6 is present in 26% of SPF herds, serotype 2 in 17%, serotype 7 in 0.4%, and serotype 5 in 0.1% (5). Studies have shown that vaccines against APP can reduce the prevalence of pleuritis (16, 17). Vaccines against APP are the third most frequently used type of vaccines in Danish pig production, representing 8% of the vaccine dosages prescribed in 2013 (10).…”
Section: Introductionmentioning
confidence: 99%